HIDDEN HISTORIES: Deaf Lives Ireland - (:unkn) unknown (Interesource Group, 2012)
A booklet issued on the Irish part of the European-wide project: Hidden Histories: Intercultural Dialogue and Learning - administered by Community Engagement Unit in the University of Sussex. This booklet accompanies the online website which contains several video-clips in Irish Sign Language and their written English transcripts. http://deaflivesireland.omeka.net/items/show/23537
Keywords: Deaf studies; Ireland; Irish Sign Language